Pengaruh Konsentrasi PVA Terhadap Analisa Merkuri Menggunakan MEtode Spektrofotometer UV-Vis - Dewi, Listiyana Candra (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2019)
Not all mercury complex compounds can be stable for a long time. Some require additional stabilizers to keep mercury concentrations in the sample unchanged due to interference from outside factors such as measurement time, temperature, humidity, and light. One of the stabilizing compounds commonly used in the analysis of complex compounds is Polyvinyl Alcohol (PVA). Addition of certain substances in the sample solution will have an influence on the character of the sample solution. In this article we will discuss the effect of PVA concentration on the results of analysis of mercury iodide-rhodamine B complex using a UV-Vis spectrophotometer method. The research in this article is experimental. Measurements are made by changing the Hgcation2+ to anion [HgI4]2-. The anion was reacted with rhodamine B and PVA compounds with varying concentrations, then analyzed using a UV-Vis spectrophotometer. The presence of mercury in solution gives rise to new peaks in the wavelength range of 592-606 nm. The concentration of PVA added as a stabilizing agent affects the measurement results. The more concentrated PVA concentration is used, the lower the peak of the mercury iodide-Rhodamine B complex on the spectrum.